Development of functional probiotic yogurt from buffalo milk supplemented with red beetroot (Beta vulgaris L.) as an antioxidant, natural colorant, and starter growth stimulant - Khaled H. Salman; Taha Mehany; Khaled G. Zaki; Mohammed K.W. Al-Doury (Food Chemistry Advances)
The physicochemical, sensorial, and probiotics viability properties of supplemented probiotic yogurt with beet juice (BJ) at various ratios (0–5)% in fresh and stored yogurts were determined. 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging activity (%) and minerals content of BJ-yogurts were increased. The color aspects (ΔE) were improved with the increasing of BJ. BJ-yogurts at 1 and 3 % were color-stable when stored in the refrigerator (5 ± 1 °C) for 9 days. The syneresis reached of 42.9, 43.0, 43.5, and 43.5 mL for control, 1 %, 3 %, and 5 % BJ, respectively in stored yogurts for 12 days. Moreover, the probiotic yogurt viability in BJ-yogurts treatments was found to be higher (p < 0.05) than control which recorded of 7.0 ± 0.08, 7.22±0.04, 7.34±0.002 log cfu/mL for streptococci, lactobacilli, and bifidobacteria counts respectively in 5 % BJ treatment, on the other hand, in control recorded of 6.76±0.07, 7.11±0.06, 6.66±0.030 log cfu/mL for streptococci, lactobacilli, and bifidobacteria counts respectively; indicating that BJ had a stimulating effect on the additive starter. Fresh yogurts with 1 % BJ had superior sensorial scores than other treatments, and generally maintained desirable organoleptic attributes for up to 9 days. This study provides a nutritious, low-cost, stable, and attractive colored yogurts from buffalo milk without negative impact on physiochemical qualities.